1985
DOI: 10.1103/physrevc.31.2199
|View full text |Cite
|
Sign up to set email alerts
|

Decay of 2.22-secBa901

Abstract: The decay of '56Baqo to levels of odd-odd 57La8& has been studied in experiments in which yyt coincidence, yet(0) angular correlation, y-ray singles, and time-dependent y-ray spectra were collected. The ' Ba activity was produced directly by on-hne mass separation from the fission products of the 'U(n, h, f) reaction. The half-life of ' Ba was determined to be 2.22+0.07 sec. A level scheme containing 48 levels and 231 y rays is proposed for '~L a. Spin and parity for some levels below 1.2 MeV are assigned on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Relative γ-ray intensities have been determined from the observed number of counts in the β − γ singles spectrum, corrected for γ-and β-detection efficiency, such that the 2 [32]. It is assumed that this isomer is not populated and the 141-keV transition has an absolute intensity I γ = 20.2(20)% [30].…”
Section: γ-Ray Intensitiesmentioning
confidence: 99%
“…Relative γ-ray intensities have been determined from the observed number of counts in the β − γ singles spectrum, corrected for γ-and β-detection efficiency, such that the 2 [32]. It is assumed that this isomer is not populated and the 141-keV transition has an absolute intensity I γ = 20.2(20)% [30].…”
Section: γ-Ray Intensitiesmentioning
confidence: 99%
“…Similarly, the lowlying non-yrast transitions of the neighboring La isotopes 142 La and 146 La were investigated by means of β − decay by Chung et al (see Refs. [20] and [21] and the earlier publications therein). As is well known, exploration of the high-spin yrast and near-yrast spectroscopy for neutronrich nuclei was greatly enhanced by the advent of large gamma-detector arrays in combinations with fission [8].…”
Section: Introductionmentioning
confidence: 91%
“…The ground state of the odd-odd lanthanum isotopes with 140 A 146 have been generally assigned odd parity based on β − decay studies from 0 + parent ground states, and on shell model considerations [18][19][20][21]. We accept the assignments for the ground and 16.3-keV states of 3 − and 4 − of 144 La, respectively.…”
Section: Nuclear Level Schemesmentioning
confidence: 99%
“…The 121.16-keV level 1 − , 2 − (1 − , 2 − , 3 + ): Our results are compatible with the transition being either pure E1 or M1/E2 mixed character, although the M1 component would be significantly enhanced. Chung et al [41] suggested that the results from angular correlations (372-121-0 keV states cascade), favoured the 1 + → (1 − , 2 − ) → (2 − ) cascade. However, given the relatively large uncertainties in the A 22 and A 44 parameters, spin 2 and 3 can also reproduce the data.…”
Section: Lamentioning
confidence: 99%
“…The 140.85-keV level (2 − 2 ) (2 + 1 ): The 140.7-keV transition is the only one observed to depopulate this state and, by employing angular correlations with the 232-keV transition, it was assigned δ = 0.66 (13) [41]. The upper limit for the lifetime observed for this level yields an nonphysical B(E2)> 376 W.u.…”
Section: Lamentioning
confidence: 99%